Prioritising Facilities Management Services for Benchmarking in Selected Cities in Nigeria - Adewunmi, Yewande; Omirin , Modupe; Koleoso, Hikmot (Penerbit Universiti Sains Malaysia, 2016)
Due to the high cost of benchmarking, it is often difficult to provide required resources for it. Therefore, to benchmark successfully, it is often necessary to identify services that are most important for the efficiency of the organisation and prioritise them. This paper examines the facilities management (FM) services that are most in need of benchmarking in Nigeria. Data were collected through self-administered questionnaires that were sent to 120 facilities management organisations in Lagos metropolis, 50 in Abuja and 15 in Port Harcourt. The survey achieved a total response rate of 76% in Lagos, 58% in Abuja and 87% in Port Harcourt respectively. The five services that need benchmarking the most were found to be: utilities, maintenance, security, cleaning and waste disposal, property management and Information Technology in that order. Also, repeated measures analysis of variance results showed that the differences indicated in the respondents' rating of how important it is to benchmark these FM services is statistically significant. Kruskal Wallis test showed that there was difference in the importance of FM services for benchmarking based on professional affiliation of the FM. The study provided information on how to prioritise these services for benchmarking in order to conserve resources of Nigerian organisations.